Effect of Firm Size and Leverage on Earning Management - Ghofir, Ade; Yusuf, Yusuf (Journal of Industrial Engineering & Management Research, 2020)
Financial reports provide all the information needed for stakeholders, especially investors, and what investors pay attention to is profit as a proxy for management performance and performance. The more professional the company management is, the more investors' perception is that the more profit is generated. Investors rarely analyze the issuer's condition more fundamentally. Because profit is often the center of attention of investors, thus encouraging management to do things that are not appropriate, namely making the entity look good financially or known as Earnings Management. This study aims to analyze the effect of firm size and leverage on earnings management. The samples of this study were companies in the food and beverage sub-sector on the Indonesia Stock Exchange that published their financial reports in 2014-2018. Data were analyzed using the multiple regression method with the SPSS 23.00 analysis tool. The results showed that firm size and leverage had no significant effect on earnings management.